The Need for Development of Medical Genetics and Genomics Curriculum for Medical Schools in Saudi Arabia - Al-Harbi, Khalid M. (International Journal of Innovative Research in Medical Science, 2019)
Next generation genomic tools including dense SNP arrays and high throughput sequencing technology have led to the exponential increase in delineating genetic defects in rare as well as common genetic disorders. Advanced genetic tools have found clinical applications in almost all areas of medicine specifically in clinical diagnostic setting. Genomic testing has entered clinical practice and physicians are using genomic information to guide treatment options. Medical schools throughout the world have integrated medical genetics and genomics courses in the curriculum to prepare medical students and future physicians to understand the role of genetic factors in human health and disease. However, in Saudi Arabia, the existing undergraduate curriculum in most of the medical schools is insufficient to prepare medical students to cope with rapidly advancing genomic science. Moreover, the majority of medical schools in Saudi Arabia have no geneticist as an academic staff, and where there are such academician available relatively less teaching time is allocated for them and negligible use is made of their specialized knowledge. Overall in Saudi Arabian medical schools, little genetics teaching is given to medical students. An objective oriented genetic and genomic course need to be integrated in medical school curricula which would subsequently prepare generation of the student who can develop a critical understanding and knowledge of core concepts in medical genetics and genomics.